Implementasi Kebijakan Program Jaminan Kesehatan Nasional Kartu Indonesia Sehat Untuk Masyarakat Miskin (Studi Di Puskesmas Wua-Wua Kota Kendari) - Safira Safira; Arifin Utha; Akhyar Abdullah (REZ PUBLICA : Jurnal Administrasi Negara, Politik-Pemerintahan & Hubungan Internasional, 2021)
This study aims to determine the role of implementing the national health insurance program policy for the healthy Indonesia card for the poor at the Wua-Wua Public Health Center, Kendari City and to determine the factors that influence the implementation of the national health insurance program policy for the healthy Indonesia card for the poor at the Wua-Wua Health Center. Kendari City. The research methodology used in this study is a descriptive method that seeks to describe the intended phenomenon. The data obtained from the results of interviews with informants amounted to 7 people who were directly involved and knew about the role of implementing policies for the National Health Insurance Program for the Healthy Indonesia Card for the poor. Which then the data obtained and then analyzed then interpreted and drawn a conclusion.The results of this study are based on the results of the analysis and discussion that have been described, that the implementation of the policy of the national health insurance program for the healthy Indonesia card for the poor at the Wua-Wua Public Health Center Kendari City consists of 2 frameworks, namely the implementation of the national health insurance program for the healthy Indonesia card which consists of communication indicators, resources and disposition. Then further about the factors that influence the implementation of the policy of the National Health Insurance Program for the Healthy Indonesia Card. Keywords: Implementation; National Health Insurance Program for the Healthy Indonesia Card.